The adversary or the devil? Semantic analysis of wiþer-nouns in Old English - Sylwanowicz, Marta; Wojtyś, Anna (My University, 2020)
The examination of Old and Middle English religious lexis has attracted attention of many scholars. However, there are hardly any studies that would offer a comprehensive diachronic analysis of the terms denoting ‘Satan/(the)Devil’. The authors of the present study aim to fill this gap by conducting a systematic analysis of early English lexical field of ‘(the) evil spirit’, beginning with the analysis of Old English items that could potentially refer to ‘Satan/(the)Devil’ This paper discusses wiþer-nouns in Old English with the aim to verify which of them were applied with reference to ‘(the) evil spirit’. Thus, the texts compiled in the Dictionary of Old English Corpus have been searched for all the above-listed items. The identification of their uses has allowed us not only to determine the frequency of the words in question but also to specify whether the sense of ‘(the) evil spirit’ was core or peripheral for each lexeme.
Keywords: Old English lexis; wiþer; agent nouns; (the) Devil; evil spirit; corpus study